The Role of Vascular Endothelial Growth Factor in Tendon Healing - Liu, Xueli; Zhu, Bin; Li, Yujie; Liu, Xinyue; Guo, Sheng; Wang, Chenglong; Li, Sen; Wang, Dingxuan (Frontiers in Physiology, 2021)
Angiogenesis is crucial to facilitate tendon healing, such as delivering oxygen and nutrients, removing waste products, and controlling immune responses. Vascular endothelial growth factor (VEGF) is one of the most vital angiogenic factors that regulate blood vessel formation in tendon healing. Recently, biological therapies, including the application of exogenous VEGF, have been attracting increasing attention. However, at present, the effect of the application of exogenous VEGF in tendon healing is controversial, as the role of endogenous VEGF in tendons has also not been fully elucidated. This article will summarize the role of both endogenous and exogenous VEGF in tendon healing and discuss possible reasons for the controversy. The present review shows that tendon repair is facilitated only by proper angiogenesis and VEGF at the early stage, whereas the persistent high VEGF expression and prolonged presence of blood vessels may impair tendon repair at a later stage.